We are how much we Eat: Nutrient-Specific Versus Calorie-Based Adult-Equivalent Scales - Ali, Mohammad; Villa, Kira M (Agriculture and Food Sciences Research, 2022)
The accurate conversion of household-level food availability into individual-level nutrient availability depends on which adult-equivalent scale is employed. The purpose of this paper is to come up with a set of adult-equivalent scales based on the specific daily intake requirement for macro- and micronutrients. Using t-tests on household-level data from Nepal, we also attempt to find whether on average there are differences between the individual-level nutrient availability estimates when they are calculated through nutrient-specific versus calorie-based, per capita, or Organization for Economic Cooperation and Development (OECD) adult-equivalent scales. The results suggest that on average there are significant differences between the individual-level nutrient availability estimates depending on which adult-equivalent scale is used. Finally, we find that nutrient-income elasticities calculated through different adult-equivalent scales are statistically different from each other. Thus, the nutrient-specific adult-equivalent scales derived in this paper have the potential to reduce measurement error in future studies.